EDUCATION SYSTEM IN GUPTA PERIOD - Tewari, Kamlesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2021)
This study examines the education system during the Gupta period in this paper aims to study: The Gupta Dynasty (319-550 CE): Its Structure, Curriculum, and Contribution to Ancient Indian Knowledge. Specifically, the paper explores: 1. Organization and structure of education during the Gupta Dynasty 2. Curriculum and subjects taught at different levels of education 3. Contribution of the Gupta education system to ancient Indian knowledge and its legacy In essence, the paper seeks to understand how education was imparted during the Gupta Dynasty and its impact on ancient Indian society and knowledge.